Application of a Ni mercaptopyrimidine MOF as highly efficient catalyst for sunlight-driven hydrogen generation1. Issue 13 (7th April 2015) - Feng, Yanan; Chen, Chi; Liu, Zhuguang; Fei, Binjie; Lin, Ping; Li, Qipeng; Sun, Shigang; Du, Shaowu
<x xml:space="preserve">Abstract</x> A 2D Ni/S MOF was prepared, which could function as an efficient heterogeneous catalyst for sunlight-driven hydrogen production in water.